2016
DOI: 10.1016/j.phrp.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Spermarche and Menarche are Associated with Physical Activity and Sedentary Behavior Among Korean Adolescents

Abstract: ObjectivesThis study examined the timing of menarche and spermarche and their associations with physical activity (PA) and sedentary behavior (SB) after controlling for body mass index (BMI).MethodsMultiple logistic regression analyses were conducted to determine whether the timing of menarche in girls and spermarche in boys is associated with PA and SB independent of BMI in a nationally representative sample of Korean adolescents (13–18 years; N = 74,186).ResultsAfter controlling for age, family economic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This could explain why the correlation between health and development does not appear to be stronger when gleaned from osteological analyses. Moreover, there is a lack of knowledge about male development, with existing studies focusing mostly on non‐European populations (e.g., Lee, Pabayo, & Kawachi, 2016; Song, Ma, Wang, Lau, & Agardh, 2015) or overweight children (e.g., De Leonibus et al, 2013 ) . Additionally, biological and medical literature has shown that puberty, especially in girls, can be expedited due to psychological stress, and to a lesser extent due to physical stress (Hochberg & Belsky, 2013; Louis et al, 2008; Proos & Gustafsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why the correlation between health and development does not appear to be stronger when gleaned from osteological analyses. Moreover, there is a lack of knowledge about male development, with existing studies focusing mostly on non‐European populations (e.g., Lee, Pabayo, & Kawachi, 2016; Song, Ma, Wang, Lau, & Agardh, 2015) or overweight children (e.g., De Leonibus et al, 2013 ) . Additionally, biological and medical literature has shown that puberty, especially in girls, can be expedited due to psychological stress, and to a lesser extent due to physical stress (Hochberg & Belsky, 2013; Louis et al, 2008; Proos & Gustafsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lack of athleticism appears to result in early menarche [110] while specific sports appear to result in typical age of menarche [111]. However, a Korean study reported conflicting results, with early and late menarche observed among girls participating in physical activity and normal menarche observed for those with sedentary activity [112]. Therefore, it is possible that the specific type of physical activity could affect timing of menarche, but likely not physical exercise in general, given the conflicting results.…”
Section: Disease Causes and Consequencesmentioning
confidence: 99%
“…In a previous study, pubertal timing was defined as grade of first spermarche in boys. 16 This same definition was applied, and the average grade of the first spermarche was calculated for all subjects except those who had not yet experienced spermarche. The participants were divided into four groups based on the average grade at spermarche: group 1 (spermarche occurred earlier than the average grade), group 2 (average), group 3 (spermarche occurred later than the average grade), and group 4 (had not yet experienced).…”
Section: Methodsmentioning
confidence: 99%